Pinch analysis for targeting desalinated water price subsidy - Jia, Xiaoping (Animo Repository, 2019)
Seawater desalination is useful for supplementing the freshwater supply to coastal industrial parks. However, high cost and energy consumption is a serious disadvantage of typical desalination plants. Subsidy from government can incentivize investments to increase supply of desalinated water. However, the subsidy must be calibrated to minimize cost to the public. A graphical pinch analysis method is developed to determine the optimal subsidy for water desalination, taking into account local water price as well as supply and demand. This method uses the Limiting Composite Curve (LCC)as basis for the optimal subsidy; the minimum quantity of desalinated water is also determined. Next, the minimum subsidy is determined by relaxing the subsidized price of desalinated water. The proposed method is demonstrated through an illustrative industrial park case study. Results show that the optimal subsidy for desalinated water is $0.35/t. Sensitivity analysis shows that, when subsidy increases, demand for desalinated water increases and displaces the demand for other water resources. Furthermore, analysis of the Water-Energy Nexus is conducted to find the minimum energy consumption per unit of water at the optimal subsidy level. The proposed method can provide options for the industrial park to achieve the economic development, while minimizing the environmental impact of water supply mix. © 2019 Elsevier Ltd